2021
DOI: 10.1371/journal.ppat.1009225
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 tropism, entry, replication, and propagation: Considerations for drug discovery and development

Abstract: Since the initial report of the novel Coronavirus Disease 2019 (COVID-19) emanating from Wuhan, China, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has spread globally. While the effects of SARS-CoV-2 infection are not completely understood, there appears to be a wide spectrum of disease ranging from mild symptoms to severe respiratory distress, hospitalization, and mortality. There are no Food and Drug Administration (FDA)-approved treatments for COVID-19 aside from remdesivir; early efforts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(197 citation statements)
references
References 112 publications
8
169
0
Order By: Relevance
“…Mechanistically, the different infectivity of cells expressing high levels of TMPRSS2 is probably explained by the fact that WT SARS-CoV-2 S is cleaved at the furin cleavage site (S1/S2 cleavage), which primes S for cleavage with TMPRSS2 (at S2’) resulting in activation of the fusion peptide 1 . The virus can then fuse at the plasma membrane to enter cells 20, 22 . It has been shown that the furin-cleaved S can also interact with neuropilin (NRP1) following the CendR rule, potentially enhancing viral entry 34, 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the different infectivity of cells expressing high levels of TMPRSS2 is probably explained by the fact that WT SARS-CoV-2 S is cleaved at the furin cleavage site (S1/S2 cleavage), which primes S for cleavage with TMPRSS2 (at S2’) resulting in activation of the fusion peptide 1 . The virus can then fuse at the plasma membrane to enter cells 20, 22 . It has been shown that the furin-cleaved S can also interact with neuropilin (NRP1) following the CendR rule, potentially enhancing viral entry 34, 35 .…”
Section: Discussionmentioning
confidence: 99%
“…1A) and apilimod (Fig. 1B) (19,25,26). While this mutation has no effect on the virus entry mechanism or sensitivity to proteases, it stabilizes the stalk region of the spike, which otherwise tend to fall apart after furin cleavage between S1 and S2 (27)(28)(29)(30).…”
Section: Combined Use Of Apilimod and Camostat Mesylate Led To Enhanced Inhibition Of Vsv-mentioning
confidence: 99%
“…Then the genomic RNA undergoes replication and translation to form new virions after assembly in ERGIC, and the new viruses then are released into the outside of the cell. 43 , 44 Previous studies showed that NRPs are known to mediate the internalization of CendR ligands through an endocytosis resembling micropinocytosis but it is unclear whether NRP1 allows attachment and receptor-mediated endocytosis in SARS-CoV-2 infected patients. 6 , 22 , 45 , 46 Thus, further studies need to be done to clearly explain the role of NRP1 in the entry and infection mechanisms of SARS-CoV-2.…”
Section: Neuropilin 1 and Covid-19mentioning
confidence: 99%